Diversity survey of Pholcus spiders (Araneae, Pholcidae) from eastern Sichuan and neighboring areas, with descriptions of six new species - Jinglin Li; Shuqiang Li; Xiaoqing Zhang; Zhiyuan Yao (ZooKeys)
Thirteen spider species of the genus Pholcus Walckenaer, 1805 are reported from a diversity survey in eastern Sichuan and neighboring areas (northeastern Yunnan and western Guizhou). They belong to three species groups and include six newly described species: Pholcus qiaojia Li, Li & Yao, sp. nov. (♂♀, Yunnan) in the bidentatus group; P. aba Li, Li & Yao, sp. nov. (♂♀, Sichuan) and P. wenchuan Li, Li & Yao, sp. nov. (♂♀, Sichuan) in the crypticolens group; P. mengding Li, Li & Yao, sp. nov. (♂♀, Sichuan), P. miyi Li, Li & Yao, sp. nov. (♂♀, Sichuan) and P. yaan Li, Li & Yao, sp. nov. (♂♀, Sichuan) in the yichengicus group. P. bidentatus Zhu, Zhang, Zhang & Chen, 2005 is recorded from Yunnan for the first time and P. kunming Zhang & Zhu, 2009 is recorded from Guizhou and Sichuan for the first time. Detailed diagnoses, descriptions, photomicroscope images, and DNA barcodes of all newly described species are provided.